If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.2 = -6y + 40.6 Reorder the terms: 2.2 = 40.6 + -6y Solving 2.2 = 40.6 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 2.2 + 6y = 40.6 + -6y + 6y Combine like terms: -6y + 6y = 0 2.2 + 6y = 40.6 + 0 2.2 + 6y = 40.6 Add '-2.2' to each side of the equation. 2.2 + -2.2 + 6y = 40.6 + -2.2 Combine like terms: 2.2 + -2.2 = 0.0 0.0 + 6y = 40.6 + -2.2 6y = 40.6 + -2.2 Combine like terms: 40.6 + -2.2 = 38.4 6y = 38.4 Divide each side by '6'. y = 6.4 Simplifying y = 6.4
| 2(4x-3)/34 | | -7u+11u+5=2u+31 | | X^2-7x+12=y | | 11x+5X-1=65X-26 | | 3x^5-6x^4+18x^3= | | 28b^2-2b-6=0 | | -38m^4n^16/19n^18p^3 | | ln-5n=ln(4-3n) | | 9y-4y=35 | | 6x+5-3x=28 | | 8x+32-43x=77-12x | | u^2-14u+48=0 | | 4y-(3+y)y=2 | | 3x+55=115 | | 7x-5=3(4x+5) | | -8ln-9x=-8 | | -5m-4+[3]=13 | | y-12=3y-25 | | x^2-4w-35=0 | | A^2-17ab+60b^2=0 | | 6v^2-26=-v | | y=(a-b)x+5 | | R^2+13rs-48s^2=0 | | -1-8ln(-8b-5)=7 | | (5z^5+6z)-(-8z^5-7z+3)= | | 162=6x-12 | | 24=(10)b^1+17 | | 250/1=.75/x | | 2n+3.75+7n+10n-2.25=180 | | (2x)(2x)=5x | | 4/5×y=60 | | 5/10=x/40 |